Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a) <=> 4sinxcosx -(2cos2x-1)=7sinx+2cosx-4
<=> 2cos2x+(2-4sinx)cosx+7sinx-5=0
- sinx=1 => 2cos2x-2cosx+2=0
pt trên vn
b) <=> 2sinxcosx-1+2sin2x+3sinx-cosx-1=0
<=> cos(2sinx-1)+2sin2x+3sinx-2=0
<=> cosx(2sinx-1)+(2sinx-1)(sinx+2)=0
<=> (2sinx-1)(cosx+sinx+2)=0
<=> sinx=1/2 hoặc cosx+sinx=-2(vn)
<=> x= \(\frac{\pi}{6}+k2\pi\) hoặc \(x=\frac{5\pi}{6}+k2\pi\left(k\in Z\right)\)
Lời giải:
PT $\Leftrightarrow 2\sin 2x\cos 2x+2\cos 2x+4(\sin x+\cos x)=1+\cos ^22x-\sin ^22x=2\cos ^22x$
$\Leftrightarrow \sin 2x\cos 2x+\cos 2x+2(\sin x+\cos x)=\cos ^22x$
$\Leftrightarrow \cos 2x(\sin 2x+1-\cos 2x)+2(\sin x+\cos x)=0$
$\Leftrightarrow \cos 2x(2\sin x\cos x+2\sin ^2x)+2(\sin x+\cos x)=0$
$\Leftrightarrow \cos 2x\sin x(\cos x+\sin x)+(\sin x+\cos x)=0$
$\Leftrightarrow (\sin x+\cos x)(\cos 2x\sin x+1)=0$
Nếu $\sin x+\cos x=0$. Kết hợp $\sin ^2x+\cos ^2x=1$ suy ra $(\sin x, \cos x)=(\frac{1}{\sqrt{2}}; \frac{-1}{\sqrt{2}})$ và hoán vị
$\Rightarrow x=k\pi -\frac{\pi}{4}$ với $k$ nguyên.
Nếu $\cos 2x\sin x+1=0$
$\Leftrightarrow (1-2\sin ^2x)\sin x+1=0$
$\Leftrightarrow (1-\sin x)(2\sin ^2x+2\sin x+1)=0$
$\Rightarrow \sin x=1$
$\Rightarrow x=2k\pi +\frac{\pi}{2}$ với $k$ nguyên.